The Modi Factor: The Role Of Narendra Modi’s Idiosyncratic Factors In India’s Foreign Policy Responses Towards China Pakistan Economic Corridor - Anak Agung Banyu Perwita (Andalas Journal of International Studies (AJIS), 2019)
The development of the China-Pakistan Economic Corridor (CPEC), as part of the Belt and Road Initiative (BRI), is one of the causes of worsening Sino-Indian relations in recent years. The Economic Corridor runs through Pakistan-occupied Kashmir, which India has claimed as its territory for decades. India sees thie Project as a violation of its sovereignty, but China defends the Project, saying that it is purely an economic connectivity project without strategic purposes. Seeing the possible worsening relations, India initiated to invite Xi Jinping for an Informal Summit with Narendra Modi. With a longstanding historical relationship with China, and his personal style diplomacy, Modi manages to fix some misconception with Xi Jinping on several issues. While trying to fix Sino-Indian relations, Narendra Modi is at the same time still firm on its opposition towards the Project. The authors observe that Narendra Modi’s personality plays a big role in India’s response towards China-Pakistan Economic Corridor. Modi’s strong and assertive personality, coupled with his Hindu-nationalist belief, explained the Indian decision to firmly opposing the CPEC. On the other hand, the footprints of Modi’s charisma, personal-style diplomacy, and his longstanding relationship with China, are visible in the Wuhan Summit, in which Modi became the spearhead of diplomacy.